1974
DOI: 10.1002/macp.1974.021751008
|View full text |Cite
|
Sign up to set email alerts
|

Study of radical polymerization by means of ESR, 2. Homogeneous polymerization of methyl methacrylate and vinyl acetate

Abstract: A very efficient ESR spectrometer was applied to the measurement of the stationary concentration of macroradicals in homogeneous polymerization. From these data the rate constants of chain propagation and chain termination for the polymerizations of methyl methacrylate and vinyl acetate were found in a direct way. Activation energies of these elementary reactions were measured. ZUSAMMENFASSUNG:Fur die Bestimmung der stationaren Konzentration von Makroradikalen bei der homogenen Polymerisation wurde ein sehr wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 5 publications
3
19
0
Order By: Relevance
“…Bresler et al reported for the first time in 1972 the application of ESR for the determination of the Arrhenius relation of the propagation rate constant for the bulk polymerization of styrene initiated with dibenzoyl peroxide and a few years later the corresponding data for MMA and vinyl acetate. [21,22] The results for styrene were later confirmed over a wide temperature range (between 0 and 130 8C) with UV initiation and different thermal initiators. [23] The k p values for other monomers have also been determined, such as for n-butyl methacrylate, [24] vinyl chloride, [25] and MMA.…”
Section: Propagation Frequency (K P [M])supporting
confidence: 59%
“…Bresler et al reported for the first time in 1972 the application of ESR for the determination of the Arrhenius relation of the propagation rate constant for the bulk polymerization of styrene initiated with dibenzoyl peroxide and a few years later the corresponding data for MMA and vinyl acetate. [21,22] The results for styrene were later confirmed over a wide temperature range (between 0 and 130 8C) with UV initiation and different thermal initiators. [23] The k p values for other monomers have also been determined, such as for n-butyl methacrylate, [24] vinyl chloride, [25] and MMA.…”
Section: Propagation Frequency (K P [M])supporting
confidence: 59%
“…To this end, a previously not investigated monomer, vinyl pivalate (VPi), was chosen ( Figure 1). Among the vinyl esters, vinyl acetate (VAc, Figure 1) has been subjected to k p determination using the EPR method, [29,30,73] the rotating sector method, [74] and PLP-SEC, [75] but the k p values obtained were not in agreement. The k p of vinyl neo-decanoate has been determined by PLP-SEC.…”
Section: à3mentioning
confidence: 99%
“…Straight lines are least squares fits. ------), [3,6,75] and for VAc determined by the EPR method in ethyl acetate (&) [82] and in bulk (~, [30] &, [82] and [73] ).…”
Section: Determination Of K Pmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these conditions for measurement are far different from practical conditions for radical polymerization. Although Bresler and coworkers 13,14 observed ESR spectra of propagating radicals of styrene and methyl methacrylate (MMA) with a specially designed cavity, the resolution of the spectra still was not good enough to understand the structure and electronic state of the propagating radicals because of their insufficient hfc's.…”
Section: Introductionmentioning
confidence: 99%